Economic and Technological Determinants of Transportation Sector Performance in Indonesia: A Panel Data Approach (2020–2024) - Etma Puji Setyowati; Hastarini Dwi Atmanti (Publikasi Inspirasi Indonesia, 2025)
This research analyzes the impact of economic and technological factors on the performance of the transportation sector in Indonesia using a panel data approach across 34 provinces during the period 2020–2024. The independent variables include the inflation rate, realization of transportation investment, and the regional digitalization index (EVDCI), while the dependent variable is the growth rate of the transportation sector. The estimation method uses panel data with a Fixed Effect Model (FEM) approach. The estimation results show that inflation and the realization of transportation investment have a positive and significant impact on the performance of the transportation sector, indicating that in the context of post-pandemic economic recovery, the increase in economic activity reflected by inflation and the realization of transportation investment also drives the demand for transportation services, while digitalization does not show a significant impact. These findings critique the short-term effectiveness of the digitalization program, which has not yet been fully functionally integrated into the national transportation system. This research emphasizes the importance of more targeted and region-based policy planning in strengthening the synergy between macroeconomic policies and the digital transformation of the transportation sector.